Cognitive Domain Impairment and All-Cause Mortality in Older Patients Undergoing Hemodialysis - Guo, Yidan; Tian, Ru; Ye, Pengpeng; Li, Xin; Li, Guogang; Lu, Fangping; Ma, Yingchun; Sun, Yi; Wang, Yuzhu; Xiao, Yuefei; Zhang, Qimeng; Zhao, Xuefeng; et al. (Frontiers in Endocrinology, 2022)
The highly prevalent cognitive impairment in hemodialysis patients is associated with all-cause mortality, however, the role of different cognitive domains impairment in this association is still not clarified. Our objective was to determine the association between cognitive domain impairment and all-cause mortality in elderly adult patients undergoing hemodialysis. We conducted a prospective cohort study including patients from 11 hemodialysis centers in Beijing. Baseline data were collected, and a series of neuropsychological batteries covered 5 domains of cognitive function were included for the assessment of cognitive function. According to the fifth version of the Diagnostic and Statistical Manual of Mental Disorders criteria (DSM-V), the patients were classified as normal, mild, and major cognitive impairment for global and domain cognitive function, then followed up for 1 year. Kaplan-Meier survival analysis was used to compare the difference in the cumulative survival rate in different cognitive domains. A multivariate Cox proportional hazards regression analysis was used to determine the association between global or domain cognitive impairment and all-cause mortality. A total of 613 patients were enrolled, the mean age was 63.82±7.14 years old, and 42.1% were women. After 49.53±8.42 weeks of follow-up, 69 deaths occurred. Kaplan-Meier plots demonstrated a significant association of cognitive impairment in memory, executive function, attention, and language domains with all-cause death. Multivariate Cox regression analysis showed that mild and major impairment of global cognition (HR 2.89, 95% CI 1.01-8.34, P=0.049 and HR 4.35, 95% CI 1.55-12.16, P=0.005, respectively) , executive cognitive domain (HR=2.51, 95%CI 1.20-5.24, P=0.014; HR=3.91, 95%CI 1.70-9.03, P=0.001; respectively) and memory cognitive domain (HR=2.13, 95%CI 1.07-4.24, P=0.031; HR=3.67, 95%CI 1.71-7.92, P=0.001; respectively) were associated with all-cause mortality. Combined impairment of 3, 4 and 5 cognitive domains were associated with all-cause mortality (HR=5.75, 95%CI 1.88-17.57, P=0.002; HR=12.42, 95%CI 3.69-41.80, P<0.001; HR=13.48, 95%CI3.38-53.73, P<0.001, respectively). We demonstrate an association between the executive and memory cognitive domain impairment and all-cause mortality in hemodialysis patients. Our data suggest that early identification of the impairments in these cognitive domains might help reduce the all-cause mortality among hemodialysis patients.